A Bibliometric Analysis of Social Media and Election Campaign Success: Mapping Research Trends from 2019 to 2023 - Nurul Wahdaniyah; Dian Eka Rahmawati; Inrinofita Sari (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This paper aims to identify trends and research mapping on the Influence of social media on the Success of Election Campaigns that have concerned academics and practitioners. The method used in this research is qualitative research with a literature study approach. The data found were 258 documents, which were then analyzed. This dataset was converted to CSV format, imported into Bibliometrix, and analyzed. The findings in this study show that the success of election campaigns is not only related to social media factors but also to the successful integration of various strategic elements in the political process. Social media platforms, including Twitter, Facebook, YouTube, and Telegram, are the main channels for delivering political messages directly to voters. This success also depends on the capacity of candidates or political parties to utilize social media effectively.